An untapped gold mine? Exploring the potential of market basket analysis to grow hotel revenue. (July 2016) - Solnet, David; Boztug, Yasemin; Dolnicar, Sara
Abstract: Market Basket Analysis identifies and predicts the purchasing behavior of customers based on the expenditure patterns of all previous customers. While widely applied in retail contexts, its use in hospitality is limited. This paper argues that Market Basket Analysis could increase revenue by enabling hotels to determine the most attractive additional products and services (beyond the room type) to offer new and repeat hotel guests. The method's potential is illustrated using five years of internal guest sales records from a luxury hotel group in Australia. Findings point to significant opportunities for hotel operators to use existing stored data to better understand purchasing decision patterns that can significantly increase revenue per transaction. Challenges to adoption and future research suggestions are offered.